1996
DOI: 10.1097/00005537-199605000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Proliferation in Nasal Polyps Could Be Up‐Regulated by Platelet‐Derived Growth Factor

Abstract: The modifications of epithelial differentiation and proliferation observed in nasal polyps (NP) could be related to local secretion of growth factors, among which platelet-derived growth factor (PDGF) could play a key role. We therefore prospectively studied, by immunohistochemistry, proliferating cell nuclear antigen (PCNA, an S-phase cell marker), PDGF, and CD-68 (activated macrophages marker) expression in NP and inferior turbinate mucosa (NM) in 11 patients. Our data show that PCNA and PDGF expression are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 17 publications
1
31
0
2
Order By: Relevance
“…21 It has also been reported that PDGF secretion by activated macrophages secreted up-regulated epithelial cell proliferation in nasal polyps. 22 However, the current report is the first to compare the protein and mRNA levels for PDGF-AA and -BB and PDGF-␣ and -␤ receptors in nasal mucosa from patients with AR, CRS without asthma, and CRS with asthma. PDGF-AA and -BB levels in nasal discharge were significantly increased in CRS with asthma, and mRNA levels for PDGF-AA and -BB were also significantly higher in nasal mucosa and polyps in CRS with asthma.…”
Section: Discussionmentioning
confidence: 88%
“…21 It has also been reported that PDGF secretion by activated macrophages secreted up-regulated epithelial cell proliferation in nasal polyps. 22 However, the current report is the first to compare the protein and mRNA levels for PDGF-AA and -BB and PDGF-␣ and -␤ receptors in nasal mucosa from patients with AR, CRS without asthma, and CRS with asthma. PDGF-AA and -BB levels in nasal discharge were significantly increased in CRS with asthma, and mRNA levels for PDGF-AA and -BB were also significantly higher in nasal mucosa and polyps in CRS with asthma.…”
Section: Discussionmentioning
confidence: 88%
“…Although the etiology of nasal polyps is still unknown, several pathological studies [4][5][6][7] have addressed the key mechanisms leading to cellular proliferation, such as epithelial cell proliferation and angiogenesis, with the results suggesting that growth factors produced by inflammatory cells could affect cell proliferation. In those studies, insulinlike growth factor I, keratinocyte growth factor, and vascular endothelial growth factor were detected in nasal polyps and were implicated in the pathogenesis of disease.…”
Section: Commentmentioning
confidence: 99%
“…Polypeptide growth factors have been shown to stimulate cell growth in various in vitro and in vivo systems. It has been reported that some growth factors, including TGFß, platelet-derived growth factor, insulin-like growth factor 1 (IGF1) and basic fibroblastic growth factor (bFGF), may contribute to cellular proliferation in NPs (11)(12)(13), thus no real-time RT-PCR experiments have been conducted for the verification of their results. RT-PCR is an established technique for quantifying mRNA expression in biological samples.…”
Section: Introductionmentioning
confidence: 99%